Peran Lembaga Penjamin Simpanan (LPS) di Era Financial Technology - Upita Anggunsuri (Nagari Law Review, 2019)
Indonesia Deposit Insurance Corporation (LPS) as the institution that has function to provide security guarantees of financial transactions should also consider the risk of the financial system built by financial Technology (Fintech). Financial Services Authority (OJK) has announced that 231 Fintech Peer to Peer Lending (P2P) are illegal. This research endeavors to answer the following questions: how is the function of LPS in Financial Technology Era and how is the readiness of Indonesia LPS in the face of Financial Technology Era. This research applied normative or legal research in answering the questions. The study concludes that even though Fintech is not the banking institution, so that deposit Fintech is not guaranteed by LPS. However, with technological developments and community needs for financial services, LPS should strive to encourage economic growth, while still doing its function to maintain the stability of financial system through the transformation of the function of Indonesia LPS, then it should form regulations that are institutionally integrated with Bank Indonesia and OJK in dealing with uncertainty about the risks caused by the Fintech industry. LPS should also prepare human resource by forming a fintech division to face the development of the fintech business